An Analysis on Conjunction Found in Barack Obama’s Speech of First Victory Election at Grant Park in Chicago - Muhammad Najib Kurnia Aji (PGRI Provinsi Jawa Timur, 2022)
This research was focused on the types of coordinate conjunction and the functions of the most type of coordinate conjunction found on the Barack Obama’s speech. This research was applied by using descriptive qualitative method. Barack Obama was the subject of this study. The source of data in this research was the scripted of Barack Obama’s first victory speech. All of the words, the phrases and/or the sentences consisting coordinate conjunctions appeared in the speech were the data in this study. The researcher was the primary instrument of the study supported by the secondary instrument called table analysis. The result showed that the most type of coordinate conjunction was ‘and’ consisting 113 items of coordinate conjunction uttered by Obama (83.09%). Meanwhile, the functions of the most coordinate conjunctions were categorized into three parts called (1) conjunctions joining words; (2) conjunctions joining groups of word; and (3) conjunctions joining parts of compound sentence. The researcher pointed out suggestions to 1) English teachers to provide clear understanding regarding the coordinate conjunction to their students, 2) students to implement their understanding in learning process, and 3) other researchers to explore the implementation of the types of conjunctions and their functions.